Mental Health and Meditation in a Post-Pandemic Perú: A Normative Study of Upper Primary School Children - Fergusson, Lee; Ortiz Cabrejos, Javier; Bonshek, Anna (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
In a post-pandemic Perú, problems associated with the mental health of children have been highlighted and effective methods of intervention have been discussed. This study sought to examine: 1) current levels of depression, anxiety, and stress in Perúvian school children; 2) how these levels compare to other children in Latin America and elsewhere; 3) whether these levels are different when covaried for school, age, gender, and grade level; and 4) whether there are any indications that depression, anxiety, or stress are lower when Perúvian school children practice Transcendental Meditation. For a group of 809 children from two schools using the DASS-21, findings indicate depression M = 6.79, anxiety M = 6.31, and stress M = 7.37. These data indicate somewhat elevated levels when compared to other pre-pandemic adolescents in Australia, Chile, China, and Malaysia, but were lower when compared to a group of similar-aged children at another school in China. Preliminary results also suggest lower levels of depression, anxiety, and stress can be observed in children who practice Transcendental Meditation as part of the school curriculum. School, age, gender, and grade level did not predict these differences, although girls had higher levels than boys, a finding consistent with other research.